Assessing Emotional Intelligence in Engineering Managers in Bulgaria and its Impact on Team Effectiveness - Demirova, Siyka; Yorgova, Juliana (Dr. Viktor Koval, 2024)
Introduction. Under the dynamic conditions of globalisation and increasing competition, modern organisations constantly seek to update their approaches to achieve efficiency and productivity in all activities. One of these approaches would be to build the emotional intelligence of the manager, which has an undeniable role in the work of a working team that achieves the set goals. Since the management of modern organisations aims to achieve efficiency in all aspects of their activities, the manager's emotional intelligence would directly affect the team's effectiveness in the organisation. It leads to a team construct, professional development of team members, and team leadership. Aim and tasks. The study aims to assess the emotional intelligence of managers from the engineering industry in Bulgaria and prove its correlation with team effectiveness. The criteria and methods of team management and the evaluation of their effectiveness in industrial enterprises were studied. The tasks were to clarify the theoretical issues of the considered problem, to examine the emotional intelligence of managers practically, and to draw conclusions about the relationship between the emotional intelligence of managers and team effectiveness in the organisation. Results. An overview analysis of the existing literature was conducted, and on this basis, the key criteria supporting the effective work of the team were derived. The emotional intelligence of middle-level management was investigated, and on this basis, the direct relationship between it and team effectiveness in the organisation was proven. The need for intervention in individual indicators to improve the team functioning of the organisation was determined based on a study of the emotional intelligence of managers. The development examined the criteria of Self-awareness, Self-management, Social awareness, and management of relationships in the team, relating to measuring the emotional intelligence of managers. The conclusions drawn are that in the surveyed enterprises, the main attention should be paid to the Social awareness criterion since the final results need to meet the modern requirements for businesses to address human resources from a social perspective. Conclusions. Evaluating the team's performance helps eliminate weaknesses and strengthen its strengths. The team is motivated and committed to achieving the set goals when this assessment is adequate and timely. The identification of criteria, factors, methods, and team performance evaluation plays a key role in managerial decision-making, providing the key to the success of team functioning in the organisation.